2016
DOI: 10.1016/j.nedt.2015.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Competencies required for nursing telehealth activities: A Delphi-study

Abstract: Many competencies for telehealth, including clinical knowledge and communication skills, are not novel competencies. They are fundamental to nursing care as a whole and therefore are also indispensable for telehealth. Additionally, the fourteen NT-EPAs appeared to require additional subject specific competencies, such as the ability to put patients at ease when they feel insecure about using technology. The NT-EPAs and related competencies presented in this study can be used by nursing schools that are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 15 publications
3
171
0
3
Order By: Relevance
“…This finding may indicate that written eCommunication is not necessarily a reduced form of face‐to‐face communication, but offers an entirely different vehicle for communication with its own unique advantages and limitations. Therefore, our findings support the findings of previous study reporting that there is a need to improve communication skills in written texts (Björk et al, ; van Houwelingen, Moerman, Ettema, Kort, & Cate, ) and that educational efforts to include written eCommunication in the nurse students curricula should be prioritized, as it is likely that text‐based consultations will expand in the future (Booth, ). Healthcare professionals and clinical educators could be a key conduit for stimulating change and increasing the focus on eCommunication.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding may indicate that written eCommunication is not necessarily a reduced form of face‐to‐face communication, but offers an entirely different vehicle for communication with its own unique advantages and limitations. Therefore, our findings support the findings of previous study reporting that there is a need to improve communication skills in written texts (Björk et al, ; van Houwelingen, Moerman, Ettema, Kort, & Cate, ) and that educational efforts to include written eCommunication in the nurse students curricula should be prioritized, as it is likely that text‐based consultations will expand in the future (Booth, ). Healthcare professionals and clinical educators could be a key conduit for stimulating change and increasing the focus on eCommunication.…”
Section: Discussionsupporting
confidence: 90%
“…This small exploratory study has a qualitative design with an Interpretive Description (ID) methodology (Thorne, 2016), which is a qualitative research strategy developed for the purpose of advancing knowledge in the applied disciplines. As ID is particularly relevant to questions arising from daily clinical practice and for developing new knowledge and insight about clinically topic that may generate changes in health care, the methodology was ideally suited to this study.…”
Section: Design/methodsmentioning
confidence: 99%
“…Some authors have described many of the desirable technology skills for clinicians as "not novel" (12), at least with regard to their profession of focus (i.e., nursing), while others suggest that what telehealth providers need is a "new skill mix" (11). We find merit in both contentions.…”
Section: Proposed Key Technology Competencies For Cliniciansmentioning
confidence: 99%
“…Furthermore, nurses should be able to demonstrate basic competencies when dealing with information systems such as basic familiarity with the use of computers, computer software applications for creating and sharing professional documents, and electronic communication tools. [10,[34][35][36][37] The findings showed that nurses highly perceived that data entered into the EHR system were important for caring their patients. They perceived the EHR system as congruent with their work routine, easy-to-use and easy-to-learn.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary nursing curricula address the need to prepare future nurses with basics of information technologies. [10,[34][35][36][37] …”
Section: Implications and Recommendationsmentioning
confidence: 99%